Application of the Waterfall Methodology in the Development of the Emcotoys System - Mia Putri Yeza; Marsya Halya Alfrida; Fauzi Adi Saputra; Capriandika Putra Susanto; Anka Luffi Ramdani; Aditya Wicaksono; Gema Parasti Mindara (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Internet technology evolution has catalyzed transformative shifts across industries, reshaping digital business operations. This research examines EmcoToys, a hypothetical toy industry case, demonstrating web application development for market expansion and product promotion enhancement. The study applied the Waterfall methodology to design and construct a website through sequential phases: requirements gathering, system design, implementation, verification, and maintenance planning. Requirements analysis distinguished between functional and non-functional specifications, while the design phase utilized Entity Relationship Diagrams and use case modeling alongside low-fidelity interface prototypes. The implementation phase leveraged Laravel and Bootstrap frameworks for front-end architecture, with SQL managing database operations. Verification procedures through black box testing validated all system functionalities with complete success rates. The maintenance strategy prioritized content management accessibility and sustainable technical architecture through contemporary frameworks. This research advances existing literature by applying the Waterfall model specifically to toy industry e-commerce development, addressing a notable research gap. The resulting system delivers measurable advantages to EmcoToys: streamlined operational workflows, expanded product market visibility, and optimized user interactions. From a practical standpoint, this work provides a structured framework for companies undertaking similar digital initiatives. Theoretically, the findings affirm the continued applicability of the Waterfall methodology for projects with well-defined parameters and moderate complexity. The project addressed inherent challenges, including restricted user input during initial development stages and database structural inconsistencies, through systematic design refinements and collaborative testing protocols. These strategic adjustments facilitated the delivery of a robust, accessible, and sustainable system aligned with organizational requirements.